2013
DOI: 10.1093/bja/aes373
|View full text |Cite
|
Sign up to set email alerts
|

Pleth variability index is a weak predictor of fluid responsiveness in patients receiving norepinephrine

Abstract: PVI was less reliable than PPV and SVV for predicting fluid responsiveness in critically ill patients receiving norepinephrine. In addition, PVI could not be measured in a significant proportion of patients. This suggests that PVI is not useful in patients receiving norepinephrine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 32 publications
2
53
1
2
Order By: Relevance
“…Almost all previous studies measured PVI at the digital site and found that PVI was dependent not only on stroke volume but also on arterial and venous compliance. 6 Confounding factors such as major vasomotor tone variations [8][9] frequently occur in high-risk patients and could explain the reported contrasting results in patients receiving norepinephrine or after cardiac surgery with CPB. [5][6][7]10 Using cephalic sensors in that setting is expected to significantly improve the PVI signal quality while simultaneously decreasing the background noise.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all previous studies measured PVI at the digital site and found that PVI was dependent not only on stroke volume but also on arterial and venous compliance. 6 Confounding factors such as major vasomotor tone variations [8][9] frequently occur in high-risk patients and could explain the reported contrasting results in patients receiving norepinephrine or after cardiac surgery with CPB. [5][6][7]10 Using cephalic sensors in that setting is expected to significantly improve the PVI signal quality while simultaneously decreasing the background noise.…”
Section: Discussionmentioning
confidence: 99%
“…4 More contrasting results have been reported in the settings of critical care and cardiac surgery. [5][6][7] In those patients, a high vasomotor tone and the frequent infusion of norepinephrine have been found to markedly alter the accuracy of PVI measurement at the digital site, [8][9][10] prompting the search for alternative anatomic sites to assess the effects of mechanical ventilation on the pulse oximeter waveform. 11 Cephalic sites (namely the ear and the forehead) could be more appropriate in critically ill and/or high-risk surgical patients.…”
mentioning
confidence: 99%
“…연속적 자동 맥압변이의 안전성 및 유효성 평가에 선택된 문헌은 총 20편으로 연구유형은 모두 진단법 평가연구였다 (Table 3) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. [정리: 편집위원회]…”
Section: 체계적 문헌고찰 및 메타분석 결과unclassified
“…A commercially available device (Masimo Set) can display an index of plethysmographic variability (PVI) on its screen in a real-time manner. Although the reliability of PVI is doubtful in patients receiving vasopressors [22], such a tool might be of great interest for the perioperative management of low-risk surgical patients, when there is no need for an invasive monitoring device or vasopressor therapy.…”
Section: Variability Of Other Surrogates Of Stroke Volumementioning
confidence: 99%